On the eigenvalues which express antieigenvalues - Morteza Seddighin; Karl Gustafson (International Journal of Mathematics and Mathematical Sciences, 2005)
We showed previously that the first antieigenvalue and the components of the first antieigenvectors of an accretive compact normal operator can be expressed either by a pair of eigenvalues or by a single eigenvalue of the operator. In this paper, we pin down the eigenvalues of T that express the first antieigenvalue and the components of the first antieigenvectors. In addition, we will prove that the expressions which state the first antieigenvalue and the components of the first antieigenvectors are unambiguous. Finally, based on these new results, we will develop an algorithm for computing higher antieigenvalues.